The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc02262d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding existing and designing novel synthetic routes to Pd-PEPPSI-NHC and Pd-PEPPSI-PR3pre-catalysts

Abstract: While investigating the formation of PEPPSI precatalysts an intermediate was isolated and proved to be suitable synthon to this pre-catalyst family. This permits the design of a novel, greener and diversity-oriented synthetic route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…of pyridine were used, high temperature was not essential, and acetone was used as a solvent. 87 The modified procedure was tested on various NHC ligands (IPr, IPr*,ICy, IPent), and all the desired compounds were obtained in good to high yields (Scheme 18). Two intermediates were isolated and investigated, which shed light on the mechanism of the reaction and confirmed that 3 eq.…”
Section: The Application Of the Weak Base Route To Palladium-and Plat...mentioning
confidence: 99%
“…of pyridine were used, high temperature was not essential, and acetone was used as a solvent. 87 The modified procedure was tested on various NHC ligands (IPr, IPr*,ICy, IPent), and all the desired compounds were obtained in good to high yields (Scheme 18). Two intermediates were isolated and investigated, which shed light on the mechanism of the reaction and confirmed that 3 eq.…”
Section: The Application Of the Weak Base Route To Palladium-and Plat...mentioning
confidence: 99%
“…Compounds 4 – 6 acted as efficient NHC‐proligands. Direct metallation of compounds 4 a , f , i – l ; 5 b – e , i ; 6 a , g , r using various metal sources, such as 7 a , b , [12d, 13c, 26] Cu 2 O, [27] Ag 2 O [28] or (tht)AuCl [29] (tht – tetrahydrothiophene), and Ni(Cp) 2 [30] (Cp – cyclopentadienyl anion), via typical procedures afforded Pd/NHC complexes 8 a – f , 9 a – f , 10 a – c , Cu/NHC complexes 11 a – c , Ag/NHC complexes 12 a – c , Au/NHC complex 13 a , and Ni/NHC complexes 14 a , b in 51–93 % yields (Scheme 6). Attempts at nickelation of compounds 4 a , i with Ni(Cp) 2 resulted in inseparable mixtures of unidentified products, whereas nickelation of compound 5 b , according to NMR data, afforded mixtures of the desired Ni/NHC complex and other reaction products (apparently formed due to involvement of the CH 2 Cl group) that were not separated.…”
Section: Resultsmentioning
confidence: 99%
“…Palladium precursors 1a-d were synthesized according to previously published procedures. 15 1 H and 13 C{ 1 H} DEPT Q nuclear magnetic reso- nance (NMR) spectra were recorded on a Bruker Advance 300 Ultrashield spectrometer at 298 K. Chemical shifts (expressed by parts per million) are referenced to residual solvent peaks (CDCl 3 : δ H = 7.26 ppm, δ C = 77.16 ppm; CD 2 Cl 2 : δ H = 5.32 ppm, δ C = 54.00 ppm). Coupling constants ( J) are given in hertz.…”
Section: Methodsmentioning
confidence: 99%
“…5 As for the trans-[Pd(NHC)(Py)Cl 2 ] (1a-d) precursors, which are commonly known as PEPPSI-type complexes (PEPPSI = Pyridine-Enhanced Precatalyst Preparation Stabilization and Initiation), they have been widely used as pre-catalysts in several cross-coupling processes 14 and can be easily prepared, as we have recently demonstrated, by reaction between PdCl 2 and pyridine and subsequent addition of the azolium salt of interest in the presence of a weak and inexpensive base, K 2 CO 3 . 15 This novel route provides access to this versatile complexes without the need of conducting reactions in neat pyridine (green acetone is used instead).…”
Section: Synthesis and Characterization Of The Palladium Complexesmentioning
confidence: 99%